Extraction and Purification of Bioactive Peptide with Antimicrobial Properties from Horseshoe Crab - Oli, Ajay K.; Shivshetty, Nagaveni; Javaregowda, Palaksha Kanive; Revanna, Kelmani Chandrakanth (Current Bioactive Compounds, 2023)
Peptides are small biomolecules that act as bioactive or host defense molecules. These peptides have a significant role in medicine because of their broad spectrum antimicrobial properties. Marine sources are the largest supply of peptides and natural small molecules since they represent half of the total global biodiversity. Among the different crab species, the horseshoe crab is widely used for extracting the peptides. The horseshoe crab is a marine and brackish water arthropod; it plays a crucial role in the reel and whelk fishing industry and the production of important pharmaceutical bioactive components. This review highlights the details of the extraction and purification of antimicrobial peptides from the horseshoe crab. These peptides represent trends and opportunities for the future, with a focus on the pharmaceutical industries.
Keywords: hemolymph